Intra-host quasispecies reconstructions resemble inter-host variability of transmitted chronic hepatitis B virus strains - (:unkn) unknown (My University, 2023)
The hepatitis B virus is a partially double stranded DNA virus in the Hepadnaviridae family of viruses that infect the liver cells of vertebrates including humans. The virus replicates through the reverse transcription of an RNA intermediate by a viral polymerase, akin to retroviruses. The viral polymerase has high replication capacity but low fidelity and no proofreading activity resulting in a high mutation rate. This contributes to the emergence of a cloud of mutants or quasispecies within host systems during infection. Several host and viral factors have been identified that contribute to mutations and mutation frequency in shaping viral evolution, however, because the dynamics of viral evolution cannot be understood from the fittest strain alone, the need exists to sequence and reconstruct intra-host diversity, recently made possible through next generation sequencing. Due to the extensive pipeline of bioinformatic analyses associated with next generation sequencing studies are needed to ascertain if quasispecies reconstruction methods and diversity measures accurately model known diversity. Here, next generation sequencing and various quasispecies reconstruction methods are used to model the natural evolution of viral populations across the full genome of hepatitis B virus strains from South Africa. This study illustrates that (i) different methods of quasispecies reconstruction reconstruct the same amount of diversity, (ii) intra-host diversity derived from full quasispecies analyses resembles diversity measures obtained from previous methods, (iii) inter-host diversity resembles the diversity between closely related quasispecies variants, (iv) diversity is increased in HIV-negative individuals, and (v) corroborate that seroconversion of HBV biomarkers increases mutation rates.
Keywords: African Research